Development of a Web-Based Counseling System for Students: A Case Study at Chatolic University of Saint Thomas - Malau, Johanes Kevin; Simangunsong, Dinda Roulita (Bahasa Indonesia, 2025)
The Catholic University of Saint Thomas provides counseling services through its Campus Ministry to support students' mental health and well-being. However, a lack of awareness regarding these services among the student body has resulted in low engagement and limited utilization. To address this issue, this study focuses on the design and development of a web-based counseling system aimed at increasing accessibility and awareness of the counseling services. By enabling students to seek guidance remotely, the system eliminates the need for in-person visits to the Campus Ministry, thereby addressing barriers such as convenience, confidentiality, and accessibility. This case study demonstrates the potential of web-based solutions to improve the effectiveness and reach of student counseling services in higher education settings.